2021
DOI: 10.12688/f1000research.26879.2
|View full text |Cite
|
Sign up to set email alerts
|

Combined vitrectomy, near-confluent panretinal endolaser, bevacizumab and cyclophotocoagulation for neovascular glaucoma — a retrospective interventional case series

Abstract: Background: Neovascular glaucoma (NVG) is a severe, potentially blinding disease and a therapeutic challenge. The purpose of this study was to evaluate the safety and efficacy of an integrative surgical approach to neovascular glaucoma. Methods: Retrospective analysis of a one-year follow-up of a consecutive interventional case series of NVG. Eyes underwent transscleral cyclophotocoagulation, pars plana vitrectomy, near-confluent panretinal photocoagulation, and intravitreal bevacizumab. Phakic eyes underwent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
3
0
2
Order By: Relevance
“…Fong et al [ 37 ] compared DCPC alone and DCPC with IVB for NVG patients and reported that DCPC alone was effective in lowering IOP in NVG patients, and the addition of IVB did not statistically enhance treatment outcomes. On the other hand, Strzalkowski et al performed CPC combined with IVB, PRP, and vitrectomy for 77 eyes with NVG, and achieved effective IOP reduction, visual acuity preservation, and the reduction of antiglaucoma medications, with phthisis bulbi as the only late complication in 3.9% of eyes [ 40 ]. We also used IVB in our study but for a different purpose; IVB was employed to improve outcomes of TLE–MMC in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Fong et al [ 37 ] compared DCPC alone and DCPC with IVB for NVG patients and reported that DCPC alone was effective in lowering IOP in NVG patients, and the addition of IVB did not statistically enhance treatment outcomes. On the other hand, Strzalkowski et al performed CPC combined with IVB, PRP, and vitrectomy for 77 eyes with NVG, and achieved effective IOP reduction, visual acuity preservation, and the reduction of antiglaucoma medications, with phthisis bulbi as the only late complication in 3.9% of eyes [ 40 ]. We also used IVB in our study but for a different purpose; IVB was employed to improve outcomes of TLE–MMC in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Despite adequate PPV and endolaser PRP, these patients may require intravitreal anti-VEGF injections in the future due to nonresolving retinal/iris NV. [151][152][153] Management of glaucoma can be performed either with trabeculectomy or glaucoma drainage device (GDD) insertion. In general, trabeculectomy has a high failure rate in eyes with NVG.…”
Section: Neovascular Glaucomamentioning
confidence: 99%
“…Eine rezente Studie aus Würzburg zeigte verhältnismäßig günstige Ergebnisse für eine einmalige Operation mit einer Kombination aus einer transskleralen Diodenlaser-Zyklophotokoagulation (20 Herde), einer Pars-plana-Vitrektomie mit nahezu konfluenter Endolaserkoagulation von den Gefäßbögen bis zur Ora serrata und einer intravitrealen Bevacizumab-Eingabe [54]. Bei phaken Augen wurde zusätzlich eine Katarakt-Operation durchgeführt.…”
Section: Merkeunclassified